Knowledge, Attitude and Behavior of Baby Caregiver’s about Management of Dairy Milk - Sarni Anggoro (GLOBAL HEALTH SCIENCE GROUP, 2020)
Breast milk is a staple food for babies. The World Health Organization (WHO) and the Indonesian Pediatric Association (IDAI) recommend that exclusive breastfeeding for 6 months be continued for up to 2 years. Daycare is one of the facilities provided to help mothers in providing breastfeeding while being at work. This study was undertaken to document the knowledge, attitude, and behavior among baby caregivers and identify the related factors influencing the behavior of baby caregivers in breast milk management. A cross sectional study was conducted to collect self-administered questionnaires from 60 baby caregivers in 2018. The validity test using the product moment obtained a value of 0.886 while the r table was 0.444, so this questionnaire was declared valid. Reliability test using Cronbach's alpha obtained a value of 0.660. Bivariate analysis test was performed using the Spearman’s rank correlation statistical test. Multiple regression models were used to analyze the association between knowledge, attitude, and breast milk management behaviors of baby caregivers. 42 of the respondents (70%) had a good level of knowledge on breast milk management, while 49 (81.66%) were good in terms of attitude, and 34 (56.77%) had satisfactory breast milk management behavior. Correlation of caregivers’ breast milk management knowledge, attitude, and behavior is statistically significant shown by the F-test result of 0,014 < 0,05. From the test results, it is found that there is an influence between knowledge and caregivers’ breast milk management behavior (p 0,000<0,05), and between knowledge and caregivers’ breast milk management attitude (p 0,001<0,05), but not between attitude and caregivers breast milk management behavior (p 0,395>0,05). The determining factors of baby caregivers’ breast milk management behavior was knowledge. Knowledge and attitude did not affect caregivers’ behavior in conducting breast milk management equally. Adequate knowledge is the major factor of baby caregivers from favorable breast milk management attitude and behavior.